Turkish folk medicinal plants, part VI: Koçarli (Aydin) - (:unkn) unknown (My University, 2007)
In this study, 68 folk medicinal plants from Koçarlι (Aydιn) are presented. Among them 53 taxa are wild and 15 taxa are cultivated plants. The folk medicinal plants are mostly used for kidney and stomach ailments, cold, hemorrhoids, diabetes, asthma and hypertension.
Keywords: Aydin; Folk medicine; Koçarli; Medicinal plants; Turkey